BIM-driven sustainable safety management solutions for downstream oil and gas (D-O&G) construction projects - Ahsan Waqar; Saad Nisar; Sarfraz Qadir (Environmental Challenges)
This research will assess how practical Building Information Modeling (BIM) has been in improving the management of safety standards for downstream oil and gas (D-O&G) building works. It is broadly evaluated concerning how it will enhance standards of safety, reduce risks at work sites, and improve general safety performance. This research is supported through structured questionnaires, wherein the questionnaire-based survey analysis would be distributed among industry professionals. Principal component analysis and bootstrapping analysis are performed to validate hypotheses developed under a comprehensive BIM-operated management framework of safety. The results reveal a strong favourable relationship between the application of BIM and management of safety, with O = 0.954 and STDEV = 0.05. Notable impacts were on variables such as areas of training in safety and collaboration, O = 0.894 and STDEV = 0.029, and incident tracking and communication, O = 0.466 and STDEV = 0.039. The research identifies key barriers and proposes strategies for effectively integrating BIM to improve safety outcomes in D-O&G projects. This research will fill this existing literature gap since it views from a relatively underexplored area: the D-O&G sector. The study, therefore, provides empirical evidence and practical recommendations to help industry practitioners and policymakers use BIM technology to develop management of safety.